Design of discrete event control systems for programmable logic controllers using T-Timed Petri nets - Jones, A.H.; Uzam, M.; Ajlouni, N. (1996 IEEE International Symposium on Computer-Aided Control System Design, 1996)
As automated manufacturing systems become more complex, the need for an effective design tool to produce both a high level discrete event control system (DECS) and a low level ladder logic implementation, becomes increasingly more important. Petri nets represent the most effective method for the design of such DECSs. The conversion of such Petri net controllers into ladder logic has been greatly simplified through the advent of the token passing logic methodology. The new technique provides a straightforward but powerful method by which to implement ladder logic code. In this paper the fundamental T-Timed Petri net structures and their associated ladder logic equivalents are described. Finally, the design of a DECS for a manufacturing system is considered. A heuristic Petri net controller is developed for the manufacturing system, and then the methodology is used to derived structured ladder logic code.